Identifikasi Pola Pemukiman Dan Saluran Pemasaran Pertanian Komoditi Hortikultura Di Kecamatan Suliki - Rizqha Sepriyanti Burano; Hani Putri; Teguh Haria Aditia Putra (Jurnal Permukiman, 2024)
Settlement patterns in rural areas will affect how the distribution of agricultural products is carried out. Efficient and strategic settlement patterns can affect the accessibility of farmers or producers to the market. This study aims to determine the settlement pattern in Suliki Sub-district and to determine the relationship between settlement patterns and marketing channels in Suliki Sub-district. This research was conducted from June to July 2023. This research is a quantitative descriptive research. This research was conducted using nearest neighbor analysis and linear regression techniques. The types of data used in this research are primary and secondary data. This is the first study conducted in Indonesia to prove that there is a relationship between settlement patterns and farmers' decisions to determine marketing channels. In previous research, it was stated that farmers' decisions to choose marketing channels are influenced by various factors, one of which is distance to the market and accessibility. These two things are indirectly formed due to the settlement pattern of the population. However, no one has clearly stated the relationship between settlement patterns and marketing channels. While in Wang's research (2021) it is stated that changes in settlement patterns occur due to the influence of several factors, one of these factors is the marketing system for agricultural products. Marketing channels are part of the marketing system. The initial hypothesis of this research is that there is a relationship between settlement patterns and marketing channels. The results of this study show that settlement patterns in Suliki Subdistrict are diverse, with two villages having a cluster pattern, three villages having a random pattern, and one village having a uniform pattern The results of this study also prove the truth of the initial hypothesis that settlement patterns have a relationship with marketing channels. This means that settlement patterns influence farmers in choosing marketing channels.